Detection of Candida species by acridine orange fluorescent dye in exfoliative smears of oral candidiasis - Kumaraswamy LR Naik; Pushparaja Shetty; Sarosh E Shroff; Vimal Kumar Karnekar; Krishna MS Prasad; Lal P Madathil (Wolters Kluwer Medknow Publications, 2014)
Background: Oral candidiasis continued to receive attention due to its evidenced association with its evidenced association with acquired immunodeficiency syndrome. In spite of considerable improvements in the laboratory diagnostic methods, there is still a need for more reliable, definitive and less time-consuming diagnostic techniques for Candida infection. Many of the studies were done utilizing acridine orange (AO) as a basic fluorescent dye for the demonstration of yeast in cultured Candida species and in histopathological sections. However, only very few studies report this technique to demonstrate Candida organisms in oral smears. The present study was carried out to assess the diagnostic reliability of detection of Candida by utilizing AO fluorescent dye in oral exfoliative smears of oral candidiasis. Materials and Methods: A total of 62 clinically diagnosed cases of oral candidiasis were studied. Two smears and a swab were collected from each suspected lesion. Each slide was stained with, periodic acid Schiff (PAS) reagent and AO. PAS stained smears were then evaluated for the presence of Candida species under light microscopy. AO stained smears were observed under fluorescent microscopy. After inoculation of swab on the saborouds agar plates, the growth of Candida species was evaluated by Gram stain and germ tube test. Each technique was evaluated for sensitivity, specificity, positive predictive value and negative predictive value. Results: It was found that the PAS stained smears were more reliable for detection of Candida species (sensitivity = 100%, specificity = 66.7%), than AO method (sensitivity = 87.5%; specificity = 0%). Conclusion: Acridine Orange fluorescent technique even though rapid lacks specificity for Candida.